The relationship between unemployment, income and interest rates toward savings / Nor Azura Atan (Faculty of Business and Management, 2007)
This study is conducted to examine the general relationship between unemployment, income and interest rates toward savings. Time period for this study is 31 years which is from year 1976 to 2006. Methodology used for this study is multiple regression analysis. In recent years it has become a common idea that high level of saving and investment is one key element of sustained economic growth. People with higher income will tend to save more on savings for better income in future. The rate of return on the investment also the key factors that influence the determinant of saving. People that do nor work do not have excess money to save. So that, the rate of saving will decrease. According to my study, there is a relationship between unemployment, income and interest rates toward savings. Unemployment and income shows the significant and positive relationship in explaining savings. While interest rates shows the significant but negative relationship in explaining savings. Since interest rates is negative relationship but the regression is acceptable because the value of adjusted coefficient of determination R-Square (R²) is near to 1. If s mean that savings is strongly explained by unemployment, income and interest rates.